Project implementation profile influencing information technology project success. A moderating effect of leadership styles and organizational culture types in Pakistan - Mughal, Muhammad Asghar (2020)
Risks and uncertainty which prevails everywhere, is an obvious aspect of all projects of information technology in Pakistan. Project delay is extra severe where cost overruns usually exceeded hundred percent of the predicted cost of the project in information technology projects in Pakistan. There are only 12% project-based IT companies in Pakistan. Failure rate is high and 60% professionals are unaware about the importance of project mature in Pakistan. The aim of the study is to increase awareness in temporary organizations and finding way to ensure project success through model development. There is need for professionals to track a consistent and rational approach to achieve certain organizational outcomes. The outcome of a project can be related to the influence of cultural, leadership, project management and critical success factors. To overcome these issues, this study applied IO critical success factors tool known as project implementation profile to facilitate professionals for project management process behavioural issues and strategic issues during project development. It can be applied to a variety of industries and organizations and is being utilized to ensure criteria. Through quantitative methodology technique, an explorative study has been adopted with close-ended questionnaires of project implementation profile and categorical moderators consisting of leadership styles and project culture types. Two hundred and twenty-three respondents were assumed usable from a population of one thousand seven hundred and twenty. Respondents were project manager, manager on project team and team members. PLS-SEM technique was employed for analysis and Top Management Support was found to be more significant and positive. Furthermore, the study developed a model based on the ranking of empirical results for the ten parameters, its criteria and its categories. Future research to be considered include accountability as a moderator with project implementation profile.